Optical Assessment of Spinal Cord Tissue Oxygenation Using a Miniaturized Near Infrared Spectroscopy Sensor - Shadgan, Babak; Macnab, Andrew; Fong, Allan; Manouchehri, Neda; So, Kitty; Shortt, Katelyn; Streijger, Femke; Cripton, Peter A.; Sayre, Eric C.; Dumont, Guy A.; Pagano, Roberto; Kim, Kyoung-Tae; et al. (Journal of neurotrauma, 2019)
Despite advances in the treatment of acute spinal cord injury (SCI), measures to mitigate permanent neurological deficits in affected patients are limited. Immediate post-trauma hemodynamic management of patients, to maintain blood supply and improve oxygenation to the injured spinal cord, is currently one aspect of critical care which clinicians can employ to improve neurological outcomes. However, without a way to monitor the response of spinal cord hemodynamics and oxygenation in real-time, optimizing hemodynamic management is challenging, and limited in scope. This study aims to investigate the feasibility and validity of using a miniaturized multi-wavelength near-infrared spectroscopy (NIRS) sensor for direct transdural monitoring of spinal cord oxygenation in an animal model of acute SCI. Nine Yorkshire pigs underwent a weight-drop T10 contusion-compression injury and received episodes of ventilatory hypoxia and alterations in mean arterial pressure (MAP). Spinal cord hemodynamics and oxygenation were monitored throughout by a non-invasive transdual NIRS sensor, as well as an invasive intraparenchymal sensor as a comparison. NIRS parameters of tissue oxygenation were highly correlated with intraparenchymal measures of tissue oxygenation. In particular, during periods of hypoxia and MAP alterations, changes of NIRS-derived spinal cord oxygenated hemoglobin (O2Hb) and tissue oxygenation percentage (TOI%) corresponded well with the changes in spinal cord oxygen partial pressures (PO2) measured by the intraparenchymal sensor. Our data confirm that during hypoxic episodes and as changes occur in the MAP, non-invasive NIRS can detect and measure real-time changes in spinal cord oxygenation with a high degree of sensitivity and specificity.